Semantics lexical structures and adjectives - Maienborn, Claudia; Heusinger, Klaus von; Portner, Paul (Mouton reader., 2019)
"Discover vital research on the lexical and cognitive meanings of words. In this exciting book from a team of world-class researchers, in-depth articles explain a wide range of topics, including thematic roles, sense relation, ambiguity and comparison. The authors focus on the cognitive and conceptual structure of words and their meaning extensions such as coercion, metaphors and metonymies. The book features highly cited material available in paperback for the first time since its publication and is an essential starting point for anyone interested in lexical semantics, especially where it meets other cognitive and conceptual research"--